Analysis of Belt Conveyor Damage in Coal Feeder Units 1-2 Using the Fault Tree Analysis (FTA) Method at PT. PLN (Persero) UPK Nagan Raya 2x110 MW - Robi Ardiansyah; Rita Hartati (Jurnal Inotera, 2022)
This research focuses on conveyor belts on coal feeder units 1-2 located in PT. PLN PLTU Nagan Raya. Belt conveyor is a tool used to move coal from coal feeder to boiler or kiln, belts from conveyor belts are made of various types of materials such as plastic, rubber, leather, metal or other materials depending on the type and nature of the material transported. The purpose of this study is to find out the root cause of the problem of conveyor belt damage in coal feeder units 1-2. The method used is the FTA (Fault Tree Analysis) method and provides a proposed improvement with the 5W + 1H method (what, why, who, when, where and how). Data collection methods are carried out in two ways, namely library studies and elevation directly into the field through interviews with the company's management. The results showed that the better the quality of coal used, the lower the number of damage that occurs on the conveyor belt.